Microbiology A Laboratory Manual - Cappuccino, James G; Sherman,Natalie (Delhi Pearson, 2005)
This comprehensive and versatile lab manual is designed for your introductory lab course in microbiology. Each of its experiments include an overview, purpose, in-depth discussion of the principles involved, easy to follow procedures, and lab reports with review and critical thinking questions - elements that will help you succeed in microbiology.
Keywords: MICROLOGY-EXPERIMENTS; MICROLOGY-LABORATORY MANUAL